The role of Msx1 and Pax9 in pathogenetic mechanisms of tooth agenesis - Yani Corvianindya Rahayu; dyah Setyorini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Tooth agenesis is one of the most common developmental anomalies in human, which one or a few teeth are absent because they have never formed, may cause cosmetic or occlusal harm, while severe agenesis which are relatively rare require clinical attention to support and maintain the dental function. Molecular studies have demonstrated that tooth development is under strict genetic control. Purpose: This article want to review the genetic regulating that are responsible for tooth agenesis especially the role of Msx1 and Pax9 in pathogenetic mechanisms of tooth agenesis. Review: Tooth agenesis is a consequence of a qualitatively or quantitatively impaired function of genetic networks, which regulate tooth development. Mutations in Msx1 and Pax9 genes are dominant for tooth agenesis in humans. The Pax9 gene, which codes for a paired domain-containing transcription factor that plays an essential role in the development of mammal dentition, has been associated with selective tooth agenesis in humans and mice. Conclusion: Reduced amount of functional Msx1 or Pax9 protein in the tooth forming cells is able to cause severe and selective tooth agenesis. There are differences in the frequency of agenesis of specific teeth associated with the defects in Msx1 and defects in Pax9.